An analysis of federal aviation administration knowledge test scores and fatal general aviation accidents - King, Bernard Francis (Kansas State University, 2015)
Over the last few years, the safety record of U.S. commercial airlines has improved to the point where the statistics on accidents are negligible. The overwhelming numbers of aviation fatalities occur in General Aviation (GA) accidents. While the fatal accident rate has improved—from around 5.0 per 100,000 miles flown in the post–World War II era to varying between 1.2 and 1.5 since 1996—it still results in 450 to 700 deaths per year. In 2013, improving GA safety was on the National Transportation Safety Board’s (NTSB’s) most wanted list. The NTSB has cited a lack of aeronautical knowledge as the cause of many of these accidents. If pilots are required to pass Federal Aviation Administration (FAA) knowledge and practical tests prior to obtaining a new pilot certificate, how could they not possess the knowledge needed to operate in the National Airspace System (NAS)? Some, attributing it to a failure to learn basic aeronautical knowledge, are concerned that potential pilots memorize the answers to test questions published in commercially available test guides and quickly forget the material after passing the test. The purpose of this retrospective causal comparative study was to see if airman knowledge tests scores are related to fatal accidents. Fatal GA accidents that had pilot error as a causal factor were compared with those in which maintenance factors caused the accidents, to see if there were significant differences in the pilots’ knowledge test scores. The time that potential pilots took to answer skill-based questions that required calculation or interpretation was compared to the time to answer recall questions to see if rote memorization may have been involved in passing the knowledge test. The results of this paper may have implications on how AFS 630 structures the FAA knowledge tests and how instructors prepare potential pilots for these tests.
Keywords: Federal Aviation Administration Knowledge Testing; Aviation Safety; Educational Tests and Measurements (0288)